Gut microbiota are related to Parkinson's disease and clinical phenotype - Scheperjans, Filip; Aho, Velma; Pereira, Pedro A. B.; Koskinen, Kaisa; Paulin, Lars; Pekkonen, Eero; Haapaniemi, Elena; Kaakkola, Seppo; Eerola-Rautio, Johanna; Pohja, Marjatta; Kinnunen, Esko; Murros, Kari; et al. (Movement disorders, 2015)
In the course of Parkinson's disease (PD), the enteric nervous system (ENS) and parasympathetic nerves are amongst the structures earliest and most frequently affected by alpha‐synuclein pathology. Accordingly, gastrointestinal dysfunction, in particular constipation, is an important non‐motor symptom in PD and often precedes the onset of motor symptoms by years. Recent research has shown that intestinal microbiota interact with the autonomic and central nervous system via diverse pathways including the ENS and vagal nerve. The gut microbiome in PD has not been previously investigated. We compared the fecal microbiomes of 72 PD patients and 72 control subjects by pyrosequencing the V1–V3 regions of the bacterial 16S ribosomal RNA gene. Associations between clinical parameters and microbiota were analyzed using generalized linear models, taking into account potential confounders. On average, the abundance of Prevotellaceae in feces of PD patients was reduced by 77.6% as compared with controls. Relative abundance of Prevotellaceae of 6.5% or less had 86.1% sensitivity and 38.9% specificity for PD. A logistic regression classifier based on the abundance of four bacterial families and the severity of constipation identified PD patients with 66.7% sensitivity and 90.3% specificity. The relative abundance of Enterobacteriaceae was positively associated with the severity of postural instability and gait difficulty. These findings suggest that the intestinal microbiome is altered in PD and is related to motor phenotype. Further studies are warranted to elucidate the temporal and causal relationships between gut microbiota and PD and the suitability of the microbiome as a biomarker. © 2014 International Parkinson and Movement Disorder Society